Capillary electrophoresis combined in‐line with solid‐phase extraction using magnetic particles as new adsorbents for the determination of drugs of abuse in human urine. Issue 9 (10th March 2016) - Baciu, Tatiana; Borrull, Francesc; Neusüß, Christian; Aguilar, Carme; Calull, Marta
Abstract : A simple approach is presented based on the in‐line coupling between magnetic particles‐based SPE and CE. Silica‐coated iron oxide particles functionalized with C18 were successfully synthesized and used as a reverse‐phase sorbent for in‐line SPE‐CE. Magnets were used to locally immobilize these sorbents inside the capillary. Four drugs of abuse were preconcentrated and determined in urine samples using the developed method with a simple pretreatment procedure based on LLE. Several parameters affecting the preconcentration were evaluated. The obtained results show that this strategy enhanced detection sensitivity in the range of 125–700‐fold compared with CE without preconcentration. The developed method provides LODs (S/N = 3) for standard samples in the range of 0.5–20 ng/mL with satisfactory analytical precision, in both intraday and day‐to‐day experiments (RSDs <20%). The LODs (S/N = 3) reached for urine samples were in the range of 20−50 ng/mL. Relative recoveries greater than 75.9% were obtained. The established method has been applied to the analysis of drugs of abuse in urine samples from drug abusers.